BRANDING AIR MINUM KEMASAN BUMDES MAKMUR ANUGERAH LESTARI CIOMAS BOGOR SEBAGAI PRODUK UNGGULAN: BRANDING AIR MINUM KEMASAN BUMDES MAKMUR ANUGERAH LESTARI CIOMAS BOGOR SEBAGAI PRODUK UNGGULAN - irmawaty; Nenah Sunarsih; Muhammad Nasoha; Sri Lestari Pujiastuti; Deni Surapto (Gandhi: Jurnal Pengabdian Kepada Masyarakat, 2025)
BUMDes Makmur Anugerah Lestari is located in the Ciomas area of Bogor. To date, this BUMDes manages several business units, one of which is a Reverse Osmosis-based refillable water service that utilizes natural spring water sources around the village. These water sources have been utilized by partners for village water management and the production of RO-based refillable drinking water. Considering the abundant water resources and the increasing demand for drinking water in the community, the Community Service team and its partners initiated a business development program through the branding of bottled drinking water. To ensure product quality and safety, water feasibility tests were conducted. According to laboratory test results, the Escherichia coli and total coliform bacteria content were both 0, thus meeting quality standards and indicating a safe level for consumption. As part of the business development strategy, training sessions were conducted on label design, packaging techniques, and water treatment processes, featuring experts in their respective fields. Through these training activities, the partners successfully designed an informative and attractive label for the drinking water product named ‘SALAQUA.’ The label visually and textually highlights the main advantages of the product, namely the use of spring water from the foot of Mount Salak. The partners produced drinking water packaging in three different sizes. The partners were able to develop the ‘SALAQUA’ drinking water product to the point where it could be positioned as the village's flagship product and has the potential to become an icon of pride for Suka Makmur Village.